Estimation of personal exposure to fine particles (PM2.5) of ambient origin for healthy adults in Hong Kong - Chen, Xiao-Cui; Chow, Judith C.; Ward, Tony J.; Cao, Jun-Ji; Lee, Shun-Cheng; Watson, John G.; Lau, Ngar-Cheung; Yim, Steve H.L.; Ho, Kin-Fai (The Science of the total environment, 2019)
Personal exposure and ambient fine particles (PM2.5) measurements for 13 adult subjects (ages 19–57) were conducted in Hong Kong between April 2014 and June 2015. Six to 21 personal samples (mean = 19) per subject were obtained throughout the study period. Samples were analyzed for mass by gravimetric analysis, and 19 elements (from Na to Pb) were analyzed using X-Ray Fluorescence. Higher subject-specific correlations between personal and ambient sulfur (rs = 0.92; p < 0.001) were found as compared to PM2.5 mass (rs = 0.79; p < 0.001) and other elements (0.06 < rs < 0.86). Personal vs. ambient sulfur regression yielded an average exposure factor (Fpex) of 0.73 ± 0.02, supporting the use of sulfur as a surrogate to estimate personal exposure to PM2.5 of ambient origin (Ea). Ea accounted for 41–82% and 57–73% of total personal PM2.5 exposures (P) by season and by subject, respectively. The importance of both Ea and non-ambient exposures (Ena, 11.2 ± 5.6 μg/m3; 32.5 ± 10.9%) are noted. Mixed-effects models were applied to estimate the relationships between ambient PM2.5 concentrations and their corresponding exposure variables (Ea, P). Higher correlations for Ea (0.90; p < 0.001) than for P (0.58; p < 0.01) were found. A calibration coefficient < 1 suggests an attenuation of 22% (ranging 16–28%) of the true effect estimates when using average ambient concentrations at central monitoring stations as surrogates for Ea. Stationary ambient data can be used to assess population exposure only if PM exposure is dominated by Ea. [Display omitted] •A wide range of trace elements were investigated for a year-long ambient and personal PM2.5 samples.•An exposure factor of 0.73 ± 0.02 was estimated using ambient PM2.5 sulfur as a surrogate.•PM2.5 of ambient origin (Ea) accounted for ~57–73% of total personal exposure by season.•Using ambient PM2.5 at central monitoring stations as proxies underestimates the true exposures by 16–28%.